A Merdeka wish for peace - Abdul Razak, Dzulkifli (New Straits Times Press (M) Bhd., 2019)
There are many factors that drive someone towards extremism. According to an expert on religion-state-society studies, geopolitical or economic influences are more likely to be the cause, although religious labelling are more often used which then makes the issues more complex. At times politicians are the culprits by using religions for their vested interest.